2013
DOI: 10.1111/tpj.12299
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of plant cell wall lignification using fluorescence‐tagged monolignols

Abstract: Lignin is an abundant phenylpropanoid polymer produced by the oxidative polymerization of p-hydroxycinnamyl alcohols (monolignols). Lignification, i.e., deposition of lignin, is a defining feature of secondary cell wall formation in vascular plants, and provides an important mechanism for their disease resistance; however, many aspects of the cell wall lignification process remain unclear partly because of a lack of suitable imaging methods to monitor the process in vivo. In this study, a set of monolignol ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
73
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 67 publications
7
73
0
Order By: Relevance
“…Assignment details are described in the Supplemental Material. caffeyl alcohol or 5-hydroxyconiferyl alcohol, and particularly with the trans-isomer (Chen et 214 al., 2012;Chen et al, 2013;Tobimatsu et al, 2013), and are clearly different from the 215 benzodioxane structure of homo-coupled piceatannols P b . The benzodioxane structures do not 216 result from the incorporation of caffeyl alcohol, nor from the related 5-hydroxyconiferyl alcohol, 217 both of which may be evidenced in the spectra of lignins from O-methyltransferase-deficient 218 plants (Ralph et al, 2001;Wagner et al, 2011), as the expected monomers from such 219 involvement in lignins were not observed here by DFRC and the characteristic aromatic signals 220 from such catechols were also not evident; all of the peaks in the HSQC spectra ( Fig.…”
Section: Nmr Examination Of the Lignins For Coupling And Cross-couplimentioning
confidence: 94%
“…Assignment details are described in the Supplemental Material. caffeyl alcohol or 5-hydroxyconiferyl alcohol, and particularly with the trans-isomer (Chen et 214 al., 2012;Chen et al, 2013;Tobimatsu et al, 2013), and are clearly different from the 215 benzodioxane structure of homo-coupled piceatannols P b . The benzodioxane structures do not 216 result from the incorporation of caffeyl alcohol, nor from the related 5-hydroxyconiferyl alcohol, 217 both of which may be evidenced in the spectra of lignins from O-methyltransferase-deficient 218 plants (Ralph et al, 2001;Wagner et al, 2011), as the expected monomers from such 219 involvement in lignins were not observed here by DFRC and the characteristic aromatic signals 220 from such catechols were also not evident; all of the peaks in the HSQC spectra ( Fig.…”
Section: Nmr Examination Of the Lignins For Coupling And Cross-couplimentioning
confidence: 94%
“…The tools to assess this prediction were recently developed, in the form of fluorescently tagged monolignol analogs, such as g-nitrobenzofuran (NBD)-tagged coniferyl alcohol (CA), that become polymerized into lignin via oxidase-mediated radical coupling (Tobimatsu et al, 2011). When applied in planta, these NBD-tagged probes were incorporated into the lignifying tissues in Arabidopsis and Pinus radiata plants (Tobimatsu et al, 2013).…”
Section: Laccase-dependent Monolignol Polymerization In Secondary Celmentioning
confidence: 99%
“…Labeling cell wall lignin using NBD-CA was carried out as follows: a mixture of 0.5 mM NBD-CA (Tobimatsu et al, 2011(Tobimatsu et al, , 2013 and 5 mM CA (Sigma) was added to liquid one-half-strength MS medium to a final concentration of 1 and 10 mM, respectively, together with 10 mM dexamethasone (Sigma) for VND7 induction. VND7-VP16-GR seedlings were incubated in this induction solution for 4 to 48 h, and they were gently shaken under regular growth conditions (listed above).…”
Section: Cell Wall Labelingmentioning
confidence: 99%
“…While antibodies and carbohydrate binding modules have proved informative [11,12], epitope masking can be problematic [13]. Click labeling of pectins has given insights into pectin secretion and its aftermath [14*] while fluorescent monolignols enable new ways to monitor the process of lignification [15*,16]. …”
Section: Introductionmentioning
confidence: 99%